Pharmaceutical Management in Response to Natural Disasters: A Systematic Literature Review - Nurlita, Diah; Satibi, Satibi; Widayanti, Anna Wahyuni; Alim, Syahirul (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Problems still occur regarding pharmaceutical supplies management in overcoming natural disasters, such as excess stock, slow distribution, staff knowledge about emergency response, logistics systems, inappropriate pharmaceuticals for the disaster type, and cross-sector coordination.Objectives: This is a systematic review of natural disasters. The results are hoped to provide recommendations to improve pharmacy management responses.Methods: Research on pharmaceutical management at natural disaster sites, covering all phases of the management process from pharmaceutical selection to disposal, original research that is fully accessible, and those published in English within 2019-2024, are the conditions for inclusion. Duplication of publications is the exclusion criteria. Databases were searched for information about pharmaceutical management for natural disasters, such as Crossref, Science Direct, PubMed, Research Gate, and Google Scholar. This study'squality assessment applied the JBI CAT checklist, and was thematically synthesized.Results: Six studies were included in the total of59.794 identified studies. The relevant characteristics of the studies are related to pharmaceutical management scope, specifically the Drug Management Cycle.Conclusion: This study concludes that pharmaceutical management in dealing with natural disasters focuses more on aspects of planning, distribution, and management support when disasters occur. The limitation of this review is the lack of research on the scope of storage, recording and reporting, evaluation, and disposal of pharmaceuticals.